Komposisi kimia minyak atsiri daun cengkeh dari proses penyulingan uap - J Jayanudin (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2011)
The chemical composition of clove leaf essential oil obtained from steam distillation process Essential oils are needed in various industries such as industrial perfumes, cosmetics, pharmaceuticals, food industry, and beverages. This study aims to determine the chemical composition of clove leaf essential oil from steam distillation process using GCMS. Dry clove leaves weighing 1.5 kg are included in the kettle flute and sealed properly. Steam from the boiler flows into the kettle with the pressure of 0.5 barG, 1 barG and 1.5 barG for 5, 6 and 7 hours. Mixture oil and water out of the condenser are accommodated and let stand for 24 hours to separate water and oil. Clove leaf oil was purified with 10% bentonite by weight of oil at a temperature of 50oC with stirring for 1 hour. Clove leaf oil that has separated from bentonite added anhydrous Na2SO4 and let stand for 15 minutes and then separate the water and Na2SO4 in oil. Samples with % yield of the largest in its chemical composition analysis using GCMS. Based on the results obtained the largest yield is 1.84% with content of eugenol is 65.03% and 20.94% trans-caryophyllene. Keywords : Clove leaf, Eugenol, Essential Oil, Steam distillationAbstrakMinyak atsiri sangat dibutuhkan dalam berbagai industri seperti industri parfum, kosmetik, farmasi, industri makanan, dan minuman. Penelitian ini bertujuan untuk mengetahui komposisi kimia minyak atsiri daun cengkeh dari proses penyulingan uap menggunakan analisa GCMS. Daun cengkeh kering seberat 1,5 kg yang sudah bersih dari kotoran dimasukkan dalam ketel suling dan ditutup dengan rapat. Steam dari boiler dialirkan ke ketel suling dengan tekanan 0,5 barG, 1 barG dan 1,5 barG selama 5, 6 dan 7 jam. Campuran minyak dan air yang keluar dari kondenser ditampung dan diamkan selama 24 jam untuk memisahkan air dan minyak. Minyak daun cengkeh dimurnikan dengan bentonit 10% dari berat minyak pada suhu 50oC sambil diaduk selama 1 jam. Minyak daun cengkeh yang telah terpisah dari bentonit ditambahkan Na2SO4 anhidrat dan diamkan selama 15 menit kemudian pisahkan air dan Na2SO4 dalam minyak. Sampel dengan % rendemen terbesar di analisa komposisi kimianya menggunakan GCMS. Berdasarkan hasil penelitian didapat rendemen terbesar adalah 1,84% dengan kadar yaitu eugenol 65,03% dan trans-caryophyllene 20.94%.Kata kunci : Daun cengkeh, Eugenol, Minyak atsiri, Penyulingan uap